Pelatihan Bahasa Inggris Bagi Pelaku Pariwisata Dengan Metode Communicative Language Teaching di Desa Wisata Penglipuran Bangli - Trisnadewi, Komang; Seriadi, Si Luh Nyoman; Putra, I Dewa Gede Rat Dwiyana; Oktarina, Putu Santi; Suhardiana, Putu Andre (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Developing tourism is not only related to facilities and infrastructure but also needs to be supported by competent Human Resources (HR), one of whom can communicate using English. The English skills possessed by some tour operators in Penglipuran Village are classified as being able to communicate. However, they still need to be improved based on the results of the pre-test given. There are still difficulties encountered both in terms of listening to English speech, understanding English reading, the ability to construct English sentences, and expressing ideas in spoken English. Thus, English language training is still needed to improve their quality. This community service activity is carried out through training through theoretical and practical presentations. The method used is Communicative Language Teaching (CLT). The activity lasts for ten meetings, with the stages of activities covering warmer core activities (speaking, writing, reading, and listening), and the last is evaluation. Overall the activity was done well, as seen from the evaluation results distributed to the training participants. All of them received a good response from the training participants. The participants' English skills also increased based on the results of the tests given to the participants.